Keselamatan di Balik Penghukuman: Menelisik Situasi Sosial Kitab Mikha - Melvin Malau (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2020)
The texts in the Book of Micah give rise to several interpretations. From several interpretations, it was written that there was a period of background in different social situations and that influenced the writing, reconstruction of the text, and message of theology. First, there is a shift in the social, political, economic, and religious situation. Second, these texts consist of several ideas, contents, and combinations. This paper presents a reading of Micah chapters 1-7 in a social-historical setting by considering its theological consequences. The research in this paper uses the social history analysis method to discuss texts as a form of meaningful language to communicate between writers, editors, composers, and listeners. The sources found are available to reconstruct the social world of ancient Israel. The results of the study emphasize that the themes of salvation after the condemnation of Micah chapters 1-7 are combined, edited during the three periods of social history namely the period pre-exile, in-exile and post-exile. Abstrak Teks-teks dalam Kitab Mikha menimbulkan beberapa penafsiran. Dari beberapa penafsiran dituliskan adanya periode latar belakang situasi sosial yang berbeda dan mempengaruhi kepenulisan, rekonstruksi peredaksian teks dan pesan teologi. Pertama, adanya pergeseran situasi sosial, politik, ekonomi, dan agama. Kedua, teks-teks ini terdiri dari beberapa ide, isi dan pengabungan-penggabungan. Tulisan ini memperlihatkan sebuah pembacaan Mikha pasal 1-7 dalam setting sejarah sosial dengan mempertimbangkan kon-sekuensi teologisnya. Penelitian dalam tulisan ini menggunakan metode analisis sejarah sosial membahas teks-teks sebagai bentuk bahasa yang bermakna untuk berkomunikasi antara penulis, redaktur, komposer dan pendengar. Sumber-sumber yang ditemukan terse-dia untuk merekonstruksi dunia sosial Israel kuno. Hasil dari penelitian menekankan bahwa tema-tema keselamatan setelah penghukuman Mikha pasal 1-7 digabungkan, diredaksi selama tiga periode sejarah sosial yaitu masa sebelum pembuangan, pembuangan dan setelah pembuangan.